School-visit by pre-service teachers: An insider view on students’ experiences and staff’s perceptions - Beylefeld, A.A.; Le Roux, A. (South African Journal of Higher Education, 2018)
In this paper we describe and interpret students’ experiences and staff’s perceptions of a school-visit project for pre-service teachers. Our developmental intention was to ascertain the worth of the intervention with a view to improve practice. As coordinators of the project, we were well placed to undertake a close-up study by giving a strong role to both fourth-year students and lecturers as evaluators of the teaching and learning context created by the intervention. Drawing on Paulo Freire’s conception of naïve consciousness, we explore the gap between students’ experiences and staff’s perceptions. Using illuminative evaluation, we provide support that the students were stimulated to become socially concerned, albeit not critically, by means of a once-off experience of unequal schooling contexts during their first year. Staff, however, indicated an awareness of what needs to be done to integrate the students’ initial experiences, and there were no real examples that they had drawn on the project to reinforce these experiences through their classroom pedagogies. We conclude the article by highlighting critical dialogue as a prerequisite for curricular reform.